Analysis of the Patient Information Quality and Readability on Esophagogastroduodenoscopy (EGD) on the Internet - P. Priyanka; Yousaf B. Hadi; G. J. Reynolds (Canadian Journal of Gastroenterology and Hepatology)
Objective. Patients are increasingly using the Internet to inform themselves of health-related topics and procedures, including EGD. We analyzed the quality of information and readability of websites after a search on 3 different search engines. Methods. We used an assessment tool for website quality analysis that we developed in addition to using validated instruments for website quality, Global Quality Score (GQS) and Health on Net (HON) certification. The readability was assessed using Flesch-Kincaid Reading Ease (FRE) and Flesch-Kincaid Grade level (FKG). 30 results of each search terms ‘EGD’ and ‘Upper Endoscopy’ from Google and 15 each from Bing and Yahoo were analyzed. A total of 45 websites were included from 100 URLs after removing duplicates, video links, and journal articles. Results. Only 3 websites were found to have good quality and comprehensive and authentic information. These websites were https://www.healthline.com, https://www.uptodate.com, and https://www.emedicine.medscape.com. There were additional 13 sites with moderate quality of information. The mean Flesch-Kincaid Reading Ease (FRE) score was 46.92 (range 81.6-6.5). The mean Flesch-Kincaid Grade level (FKG) was 11th grade, with a range of 6th grade to 12th grade and above making them difficult to read. Conclusions. Our study shows that there are quite a few websites with moderate quality content. We recommend 3 comprehensive and authentic websites out of 45 URLs analyzed for information on Internet for EGD. In addition, the readability of the websites was consistently at a higher level than recommended by AMA at 11th grade level. In addition, we identified 3 websites with moderate quality content written at 8th grade and below readability level. We feel that gastroenterologists can help their patients better understand this procedure by directing them to these comprehensive websites.